Integrated network management V integrated management in a virtual world : proceedings of the Fifth IFIP/IEEE International Symposium on Integrated Network Management, San Diego, California, U.S.A., May 12-16, 1997 - Lazar, Aurel A.; Saracco, R. (Roberto); Stadler, Rolf (Chapman & Hall, 1997)
Contains the Fifth IFIP/IEEE International Symposium on Integrated Network Management (ISINM '97) and held in May 1997, San Diego, USA. This book is useful to engineers and network managers; and as support to university courses in Telecommunications and Computer Networks.